PENGARUH PROMOSI DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN D’RAOSTOP CHICKEN dan BURGER SESKOAL JAKARTA SELATAN - Suparman Suparman; Lukman Nul Hakim; Wendy Eko Ruswanto (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This study aims to determine the effect of Promotion and Service Quality on the Level of Customer Satisfaction D'RAOSTOP Chicken and Burger Seskoal South Jakarta. This research uses quantitative methods. Data and information collection was carried out by giving questionnaires to consumers with a sample of 75 consumers with 30 statement items related to promotion variables, service quality and satisfaction levels. The results of the study stated that variable X1 (Promotion) had a positive effect on Y (customer satisfaction) of 30.33%, variable X2 (service quality) had a positive effect on Y (customer satisfaction) of 39.65% and there was an influence of promotion (X1) and service quality (X2) together on customer satisfaction (Y) by 35% while the remaining 65% is influenced by other factors outside of this study.